Mapping the terrain of person-centered supportive conversations. Issue 4 (2nd October 2018) - Jones, Susanne M.; Bodie, Graham D.; Youngvorst, Lucas; Navarro, Michael; Danielson, Carly
ABSTRACT: This study explores the conversational terrain of supportive conversations that vary in person centeredness (PC). Our team transcribed and unitized 223 conversations in which a discloser talked about an upsetting event to a listener trained to exhibit either low (LPC), moderate (MPC), or highly person-centered (HPC) comfort. Each utterance was coded for PC with a modified version of the traditional nine-level hierarchy. HPC-coded turns comprised 24% of HPC conversations, while LPC-coded turns comprised almost half of LPC conversations. Over 95% of turns in MPC conversations were classified as MPC. Additionally, turn-level coding and global ratings of PC differentially predicted outcomes. We discuss the implications of these conversational profiles in the context of how the PC content of conversations might aid in cognitive reappraisal.